PENERAPAN METODE THE LEARNING CELL DENGAN MEDIA FLANELGRAF DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SDN 4 PANDANSARI TAHUN AJARAN 2013/2014 - wijayanti, titin (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: Application The Learning Cell Methods with flanelgraf media Improved Learning in Social Studies.The purpose of research is to improve the learning of social studies material struggle fighters in Dutch and Japanese colonial period by using the method of learning cell with media flanelgraf in the fifth grade elementary school students of State 4 Pandansari. This research  is form of action research as much as three cycles. As the subject is fifth grade elementary school students of State 4 Pandansari totaling 26 students. Data collection techniques used were observation, interviews, tests, and documentation. The results showed the  application of the learning  cell with flanelgraf media can improv social studies learning materials fighters during the struggle of the colonial Dutch and JapaneseKeywords: the learning cell, flanelgraf, social studies learning Abstrak: Penerapan Metode The Learning Cell dengan media flanelgraf dalam Peningkatan Pembelajaran IPS. Tujuan penelitian untuk meningkatkan pembelajaran IPS materi perjuangan para pejuang pada masa penjajahan Belanda dan Jepang menggunakan metode the learning cell dengan media flanelgraf pada siswa kelas V SDN 4 Pandansari. Penelitian ini merupakan penelitian tindakan kelas sebanyak tiga siklus. Sebagai subjek adalah siswa kelas V SDN 4 Pandansari berjumlah 26 siswa. Teknik pengumpulan data yang digunakan adalah pengamatan, wawancara, tes, dan dokumentasi. Hasil penelitian menunjukkan penerapan the learning cell dengan media flanelgraf dapat meningkatkan pembelajaran IPS materi perjuangan para pejuang pada masa penjajahan Belanda dan Jepang. Kata kunci: the learning cell,  flanelgraf, pembelajaran IPS